2016
DOI: 10.1105/tpc.15.00997
|View full text |Cite
|
Sign up to set email alerts
|

The SUMO E3 Ligase-Like Proteins PIAL1 and PIAL2 Interact with MOM1 and Form a Novel Complex Required for Transcriptional Silencing

Abstract: The mechanism by which MORPHEUS' MOLECULE1 (MOM1) contributes to transcriptional gene silencing has remained elusive since the gene was first identified and characterized. Here, we report that two Arabidopsis thaliana PIAS (PROTEIN INHIBITOR OF ACTIVATED STAT)-type SUMO E3 ligase-like proteins, PIAL1 and PIAL2, function redundantly to mediate transcriptional silencing at MOM1 target loci. PIAL1 and PIAL2 physically interact with each other and with MOM1 to form a high molecular mass complex. In the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(85 citation statements)
references
References 68 publications
1
84
0
Order By: Relevance
“…It should be noted that PIAL1 and PIAL2 have recently been ascribed a function as (alternative) subunits of a gene silencing complex that affects mainly transposable elements (Han et al, 2016). Analysis of the transcriptome of pial1 pial2 mutants as published by Han et al (2016) indicated only five genes upregulated at the transcriptional level among our set of 56 significantly upregulated proteins (AT1G26380, AT2G14610, AT2G20560, AT4G04180, AT5G27850). In the other cases, post-transcriptional steps such as increased protein stability may be responsible for the upregulation.…”
Section: Changes In Components Of Stress Response and Regulationmentioning
confidence: 71%
See 3 more Smart Citations
“…It should be noted that PIAL1 and PIAL2 have recently been ascribed a function as (alternative) subunits of a gene silencing complex that affects mainly transposable elements (Han et al, 2016). Analysis of the transcriptome of pial1 pial2 mutants as published by Han et al (2016) indicated only five genes upregulated at the transcriptional level among our set of 56 significantly upregulated proteins (AT1G26380, AT2G14610, AT2G20560, AT4G04180, AT5G27850). In the other cases, post-transcriptional steps such as increased protein stability may be responsible for the upregulation.…”
Section: Changes In Components Of Stress Response and Regulationmentioning
confidence: 71%
“…It should be noted that PIAL1 and PIAL2 have recently been ascribed a function as (alternative) subunits of a gene silencing complex that affects mainly transposable elements (Han et al ., ). Analysis of the transcriptome of pial1 pial2 mutants as published by Han et al .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These included RTEL1, which is involved in telomere maintenance (Recker et al, 2014), and RecA2, which is required for DNA repair in organelles (Miller-Messmer et al, 2012;Recker et al, 2014). Three genes required for the maintenance of epigenetic silencing of gene expression, MOM1, STRS1 and ICU2 (Hyun et al, 2013;Khan et al, 2014;Han et al, 2016), as well as several chromatin remodellers and a histone deacetylase, also showed elevated expression levels in the hyperaccumulators (Table S6); this finding is line with the recent suggestion that chromatin compaction may increase genome stability in hyperaccumulators (Gull ı et al, 2018). (Merlot et al, 2014;Sobczyk et al, 2017).…”
Section: Senecio Coronatus Hyperaccumulators May Have Enhanced Capacimentioning
confidence: 99%